2016
DOI: 10.1590/s1517-9702201609134896
|View full text |Cite
|
Sign up to set email alerts
|

Incluindo quem? Um exame de indicadores socioeconômicos do Programa de Inclusão Social da USP

Abstract: Resumo Em 2006, a Universidade de São Paulo (USP) criou o Programa de Inclusão Social da USP (Inclusp), um sistema de pontuação acrescida, cujo principal objetivo é ampliar o número de estudantes egressos de escolas públicas (EP) na USP. Contudo, uma das críticas que esse programa recebe é a de que ele não conseguiria incluir estudantes com perfil socioeconômico muito diferente daqueles que já seriam aprovados no exame do vestibular, independentemente de sua ação. Assim, o objetivo deste trabalho é o de aprofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Concerning the equalization of opportunities, many studies described the effects of affirmative action policies on the heterogeneity of the student body. Piotto and Nogueira (2016) studied the effects of a bonus policy created in 2006 at the State University of São Paulo (USP). They observed that the proportion of students from secondary public schools and low-income families attending the university increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning the equalization of opportunities, many studies described the effects of affirmative action policies on the heterogeneity of the student body. Piotto and Nogueira (2016) studied the effects of a bonus policy created in 2006 at the State University of São Paulo (USP). They observed that the proportion of students from secondary public schools and low-income families attending the university increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interest in the education success of any individual has a great relevance and is related to broader ethical and social issues (Piotto, 2010;Piotto & Nogueira, 2016;Sánchez Pato et al, 2018;Soares, Correia, & Melo, 2016). A better knowledge on the barriers and facilitators related to dual career context allows to offer more efficient support for the student-athletes on balancing and organizing theirs school and sport routines (Álvarez-Pérez & Lópes-Aguilar, 2018;Guirola Gómez, Torregrosa, Ramis, & Jaenes, 2018;Mateu et al, 2020;Torregrosa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within this scenario, students who have more econo mic resources to invest in education commonly attend to private schools (Calçade, 2018), especially with the goal to be well prepared to take a place in a public university (Piotto, 2010;Piotto & Nogueira, 2016). As a contradiction, students with fewer economic resources that attend to public schools (basic degree) are the minority in public universities (Vitelli, Fritsch, & Silva, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to them, this might have mitigated the effect of INCLUSP. Using their main results and expanding the analysis, Piotto and Nogueira (2016) show that although more students from public schools got into USP after the AA, INCLUSP was not capable of eliminating significant barriers to the university access. Besides, Daflon, Junior and Campos (2013) suggest that, in general, bonus-based programs are less efficient in promoting access than regular quotas, and that USP would be one example of that.…”
Section: Introductionmentioning
confidence: 99%